Composting for the reduction of bird droppings (Gallus gallus domesticus) - Rosas-Martínez, Verónica; Aguilar-Rivera, Noé (Agronomía Mesoamericana, 2021)
Introduction. The growth of the population and the consumption of protein sources such as chicken meat, have maximized the generation of poultry waste (chicken manure), this leads to the development of efficient management alternatives for the conversion of this waste into by-products such as organic fertilizers. Numerous investigations conclude the remarkable effect of compost obtained from poultry waste on the development and growth of crops, which provide high content of essential nutrients as an amendment in agroecological agriculture, within the circular economy and the sustainable development of production. Objective. To carry out a review on the management plans of waste from the poultry sector through composting for use in agriculture in the region of Cordoba Veracruz Mexico. Development. The study was carried out between January and June 2020, through an exhaustive bibliographic search and the analysis of local experiences in the production of organic fertilizers with farmers. In this review and with the field work, the results established that in the region it is possible to obtain various types of compost with the incorporation of poultry waste, and the technologies of compost, vermicompost, and bocashi production individually or in a mixture with other regional by-products such as those derived from the sugar industry, coffee, livestock, etc. Nutrients such as nitrogen of 2.08-2.34 %, phosphorus 4.01-4.27 %, potassium 2.37-4.56 %, calcium 10.36-12.93, and magnesium 0.90-1.16 % are obtained and available for use. Conclusion. Poultry by-products have a great potential to generate reutilization alternatives through rural application technologies without significant investment and waste management strategies.